Tillage and residue management effect on soil properties, crop performance and energy relations in greengram (Vigna radiata L.) under maize-based cropping systems - J.R. Meena; Umakant K. Behera; Debasis Chakraborty; A.R. Sharma (International Soil and Water Conservation Research, 2015)
Effect of tillage and crop residue management on soil properties, crop performance, energy relations and economics in greengram (Vigna radiata L.) was evaluated under four maize-based cropping systems in an Inceptisol of Delhi, India. Soil bulk density, hydraulic conductivity and aggregation at 0–15 cm layer were significantly affected both by tillage and cropping systems, while zero tillage significantly increased the soil organic carbon content. Yields of greengram were significantly higher in maize–chickpea and maize–mustard systems, more so with residue addition. When no residue was added, conventional tillage required 20% higher energy inputs than the zero tillage, while the residue addition increased the energy output in both tillage practices. Maize–wheat–greengram cropping system involved the maximum energy requirement and the cost of production. However, the largest net return was obtained from the maize–chickpea–greengram system under the conventional tillage with residue incorporation. Although zero tillage resulted in better aggregation, C content and N availability in soil, and reduced the energy inputs, cultivation of summer greengram appeared to be profitable under conventional tillage system with residue incorporation.